Cerebral Ischemic Complications After Surgical Revascularization for Moyamoya Disease: Risk Factors and Development of a Predictive Model Based on Preoperative Nutritional Blood Parameters - Li, Fangbao; Li, Chuanfeng; Sun, Yunwei; Bao, Yue; Jiang, Wenbo; Song, Zuoyan; Wang, Yongyi; Liu, Mingxing; Wang, Weimin; Li, Tong; Li, Luo (Frontiers in Nutrition, 2022)
Abstract Objectives: Cerebral ischemic complications are common after revascularization in moyamoya(MMD) patients. Risk factors from specific laboratory variables have only been assessed by limited researches. This study was to investigate association between postoperative cerebral ischemia and nutritional blood parameters and examine predictive values of such risk factors in adults. Methods: Preoperative demographics and nutritional blood parameters of MMD patients who received revascularization at our institution from 2012 to 2021 were retrospectively reviewed. Univariate analysis and multivariable logistic regression were used to identify independent risk factors for the onset of postoperative cerebral ischemic complications. Predictive values were tested and a model incorporating these independent risk factors was created using R program. Area under the receiver operating characteristic curve (AUC) was used for testing its discriminability. Results: Postoperative cerebral ischemic complications occurred in 32 patients of 100 included procedures. Surgery on left hemisphere, admission modified Rankin Scale(mRS) score, aberrant nutritional parameters including low white blood cell(WBC) and high total cholesterol(TC) were significantly associated with cerebral ischemic complications after revascularization. The intriguing role of WBC might be explained by altered immunomodulation. The AUC of this model with novel nutritional parameters yielded to 0.811, presenting better predictive accuracy. Additionally, the model was visualized in form of nomogram and translated into a user-friendly calculator to generate individual risk. Conclusions: Surgical side, admission mRS score, WBC and TC were independent risk factors for postoperative cerebral ischemic complications. The model composed of these four parameters was promising to be adopted in clinical practice.